Factors of management transformation under the development of artificial intelligence - Boris, O. A.; Parakhina, V. N.; Moroz, V. V. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Generative and other models of artificial intelligence (AI) change the rules of management and business operations, bring computer technologies previously classified as auxiliary to a new level of use, reduce the time for developing solutions and provide powerful capabilities to users of different levels. Goal. The study aims to develop fundamental positions for the transformation of management systems, which are becoming increasingly important as we move from the experimental implementation of elements of generative artificial intelligence to full-fledged implementation in organizations and companies. Materials and methods. The achievability of the goal and the possibility of obtaining the expected results are ensured by using the most suitable set of methods for the study, including: analytical methods, methods of logical research and expert assessments, analysis and synthesis based on a systemic creative approach. Results and discussion. The article highlights traditional and new principles of business management based on the identification of basic changes in the factors and priorities of company leaders associated with scaling a business using artificial intelligence. The authors noted that digital transformation is not just a replacement of manual technology with digital technology, it is a change in the concept, paradigm, and model of managing an organization. The features of the transformation process are shown, the principles of using artificial intelligence and managing it are highlighted. Conclusion. The transformation of business conditions in the modern value system determines a change in the management paradigm, shifting the attention of managers from details to a holistic view of socio-economic systems.